Acetylation and phosphorylation of human TFAM regulate TFAM–DNA interactions via contrasting mechanisms. Issue 7 (21st March 2018) - King, Graeme A; Hashemi Shabestari, Maryam; Taris, Kees-Karel H; Pandey, Ashutosh K; Venkatesh, Sundararajan; Thilagavathi, Jayapalraja; Singh, Kamalendra; Krishna Koppisetti, Rama; Temiakov, Dmitry; Roos, Wouter H; Suzuki, Carolyn K; Wuite, Gijs J L
Abstract: Mitochondrial transcription factor A (TFAM) is essential for the maintenance, expression and transmission of mitochondrial DNA (mtDNA). However, mechanisms for the post-translational regulation of TFAM are poorly understood. Here, we show that TFAM is lysine acetylated within its high-mobility-group box 1, a domain that can also be serine phosphorylated. Using bulk and single-molecule methods, we demonstrate that site-specific phosphoserine and acetyl-lysine mimics of human TFAM regulate its interaction with non-specific DNA through distinct kinetic pathways. We show that higher protein concentrations of both TFAM mimics are required to compact DNA to a similar extent as the wild-type. Compaction is thought to be crucial for regulating mtDNA segregation and expression. Moreover, we reveal that the reduced DNA binding affinity of the acetyl-lysine mimic arises from a lower on-rate, whereas the phosphoserine mimic displays both a decreased on-rate and an increased off-rate. Strikingly, the increased off-rate of the phosphoserine mimic is coupled to a significantly faster diffusion of TFAM on DNA. These findings indicate that acetylation and phosphorylation of TFAM can fine-tune TFAM–DNA binding affinity, to permit the discrete regulation of mtDNA dynamics. Furthermore, our results suggest that phosphorylation could additionally regulate transcription by altering the ability of TFAM to locate promoter sites.